P07.11 Whole genome sequencing characterisation of a unique neisseria strain generating a positive result with the cobas® ct/ng test. (13th September 2015) - Honisch, C; Hibbard, S Cayabyab; Mehta, R; Phan, H; Sunkara, S; Osiecki, J; Lewinski, M; Fillmore, C
Abstract : Introduction: Neisseria gonorrhoeae (NG) cause sexually transmitted bacterial infections. The Roche cobas ® CT/NG Test is a qualitative Nucleic Acid Amplification test (NAAT) utilising a dual-target approach to detect sequences within the direct repeat (DR-9) region of the NG genome. To date, clinical performance data show excellent sensitivity and specificity for urogenital specimens. The test is validated for endocervical swabs, vaginal swabs and urine specimens. Methods: One clinical case report 1 describes a positive test result for an oropharyngeal swab, an off-label specimen type for the cobas ® CT/NG Test. This interesting Neisseria sample was subject to analysis as part of Roche's Global Surveillance Program. The isolate was tested by culture, phenotyping, whole cell MALDI-TOF MS and molecular methods such as 16S rDNA based typing and whole genome sequencing. Results: Whole genome sequencing resulted in a complete genome assembly supporting phylogenetic analysis. Sequencing data assembled into a 2, 882, 113bp contig and genome closure, which identified the sample as a Neisseria commensal species clustering in the same clade with both N. sicca and N. macacae. One partial assay specific DR-9 target region was identified within the genome of this commensal strain in the context of a phage like motif, which can facilitate genomic exchange of DNA fragments between N. gonorrhoeae and commensal strains. BLAST searches for the prophage/DR9 genetic signature of this newly characterised Neisseria strain revealed no matches to sequences in the public domain, suggesting that this strain is rare. Based on the sequence information of the prophage/DR9 genetic signature oropharyngeal swab specimens determined to be positive by the cobas ® CT/NG Test are currently being evaluated for the presence of this sequence motif. Conclusion: The cobas ® CT/NG Test on the cobas 4800 system is a reliable molecular method for detection of Chlamydia and Gonorrhoeae from genital specimens. Disclosure of interest: Authors of the abstract are employees of Roche Molecular Systems. Reference: Upton A, Bromhead C, Whiley DM. Neisseria gonorrhoeae false-positive result obtained from a pharyngeal swab by using the Roche cobas 4800 CT/NG assay in New Zealand in 2012. J Clin Microbiol . 2013;51 :1609–10